2022
DOI: 10.1021/acsaem.2c01738
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Ti3C2Tx/Carbon Nanotubes/CuS Film Electrodes Based on a Dual-Structural Design for High-Performance All-Solid-State Supercapacitors

Abstract: Freestanding and bendable films fabricated by two-dimensional (2D) MXene materials have demonstrated great potential as electrodes for energy storage devices owing to their paramount flexibility, structural stability, and high conductivity. Nevertheless, the unavoidable restacking of MXene sheets substantially limits their electrochemical performance. Here, a film electrode with a sandwich-like structure was fabricated by a dual-structural design through a layer-by-layer (LbL) method with alternating filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…For the ZnO/CuS composites, the 2 θ peak diffraction at 27.7°, 29.3° and 32.7° can be identified as the (101), (102) and (106) crystal planes corresponding to a CuS crystal (JCPDS no.06-0464). 27 Moreover, it can be clearly observed that with the increase of the mass ratio of CuS to ZnO, the characteristic diffraction peak intensity of CuS in ZnO/CuS gradually increases. In addition, no other characteristic diffraction peaks were observed, demonstrating the coexistence and good integration of ZnO and CuS in the ZnO/CuS hybrid photocatalysts.…”
Section: Resultsmentioning
confidence: 97%
“…For the ZnO/CuS composites, the 2 θ peak diffraction at 27.7°, 29.3° and 32.7° can be identified as the (101), (102) and (106) crystal planes corresponding to a CuS crystal (JCPDS no.06-0464). 27 Moreover, it can be clearly observed that with the increase of the mass ratio of CuS to ZnO, the characteristic diffraction peak intensity of CuS in ZnO/CuS gradually increases. In addition, no other characteristic diffraction peaks were observed, demonstrating the coexistence and good integration of ZnO and CuS in the ZnO/CuS hybrid photocatalysts.…”
Section: Resultsmentioning
confidence: 97%
“…7,8 In addition, the intersection with the x -axis implies the internal resistance (marked as R s ), which includes the contact resistance between the material and the NF and the intrinsic resistance of the material and electrolyte. 22…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] Among these MSs, copper sulfide (CuS) has attracted great attention due to its good conductivity and electrochemical performance. 22,23 For instance, Zhou et al reported CuS nanoflake arrays on carbon cloth using a solvothermal strategy, and obtained a capacity of 213.8 C g −1 with a longevity of 75.1% after 5000 cycles. 24 In another study, Li et al prepared porous CuS nanosheets via a solvothermal process, which exhibited a capacitance of 974 F g −1 and durability of 81.99% after 5000 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…126 The CNT in the Ti 3 C 3 T x /CNT/CuS composite avoids the restacking of MXene sheets and allows large electroactive sites to become available for the electrolyte ions. 41 Gandla et al demonstrated that Mo 2 Ti 2 C 3 MXene with larger interlayer spacing is more beneficial in ionic liquid electrolytes than conventional Ti 3 C 2 T x MXene with high specific capacitance, cycle stability, and superior energy. 127 Microsupercapacitors (mSCs) are an essential power source for portable devices.…”
Section: Electrochemical Applications Of Mxenementioning
confidence: 99%